Adjunctive Internet-delivered cognitive behavioural therapy for insomnia in men with depression: A randomised controlled trial. (April 2019) - Glozier, Nick; Christensen, Helen; Griffiths, Kathleen M; Hickie, Ian B; Naismith, Sharon L; Biddle, Daniel; Overland, Simon; Thorndike, Frances; Ritterband, Lee
Objective: Internet-delivered cognitive behavioural therapy for insomnia is efficacious for insomnia, and post hoc analyses suggest mood improvements. We undertook the first clinical trial evaluating the efficacy of Internet-delivered cognitive behavioural therapy for insomnia on depressive symptoms as an adjunct to guideline-based treatment of depressive disorders. Methods: Older men undergoing psychiatrist-coordinated treatment for major depressive disorder or dysthymia and who had significant insomnia symptoms were randomised to either adjunctive Internet-delivered cognitive behavioural therapy for insomnia (Sleep Healthy Using The Internet) or online sleep psychoeducation. The primary outcome was change in depressive symptoms (Centre for Epidemiological Studies Depression scale) from baseline to week 12 (post intervention). Secondary outcomes were insomnia and anxiety symptoms. Results: In all, 87 men were randomised (Internet-delivered cognitive behavioural therapy for insomnia = 45; psychoeducation = 42). The mean observed Centre for Epidemiological Studies Depression scale changes by week 12 were 8.2 (standard deviation = 11.5) and 3.9 (standard deviation = 12.8) for Internet-delivered cognitive behavioural therapy for insomnia and psychoeducation, respectively. The adjunctive effect size of 0.35 in favour of Sleep Healthy Using The Internet programme was not statistically significant (group × time difference in the Mixed effect Model Repeat Measurement analysis difference 4.3; 95% confidence interval = [−1.2, 9.8]; p  = 0.15). There was a statistically significant effect on insomnia symptoms (group × time p  = 0.02, difference 2.7; 95% confidence interval = [0.2, 5.3]; effect size = 0.62). There were no differences in insomnia or depression at 6 months or differential effects on anxiety at any time point. There were no reported adverse trial-related events in the intervention arm. Conclusion: Adjunctive Internet-delivered cognitive behavioural therapy for insomnia for older men being treated for depression can improve insomnia in the short term, without apparent harm. The short-term depressive symptom effect size in this pilot trial was comparable to other adjunctive interventions and may warrant a larger, definitive trial.